PERAN PEMBIAYAAN SYARIAH MELALUI BANK SYARIAH TERHADAP TINGKAT PENGEMBANGAN UMKM DI MASA PANDEMI COVID-19 - Rahmah, Naila Aulia; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2021)
Micro, small and medium enterprises (MSMEs) are businesses that play an important role in the Indonesian economy. MSMEs can hire workers, reduce unemployment and poverty. However, there are still sources of problems in the development of MSMEs, namely the low availability of funds, including the not yet optimal use of Islamic funds during the pandemic. As a result, there are currently many Islamic financial institutions that really help MSMEs during this pandemic. The purpose of this paper is to find out how the role of Islamic finance on capital in the development of MSMEs during the pandemic. The method used in this study consisted of a qualitative method with a descriptive approach. Based on the results in this paper, the role and contribution of Islamic finance in relation to capital plays an important role in the development of MSMEs during the pandemic. This provides limited opportunities for micro, small and medium enterprises (MSMEs) to develop their businesses